What makes the bonding stick? A natural experiment testing the legal bonding hypothesis - Licht, Amir N.; Poliquin, Christopher; Siegel, Jordan I.; Li, Xi (Journal of Financial Economics, 2018)
We use a US Supreme Court case, Morrison v. National Australia Bank (2010), as a natural experiment to test the legal bonding hypothesis. By decreasing the potential liability of US-listed foreign firms, particularly due to class action lawsuits, Morrison arguably eroded their legal bonding to compliance with disclosure duties. Nevertheless, we find evidence of an increase or insignificant change in share values. Tests of longer-run effects of the legal event indicate that foreign firms’ disclosure quality and likelihood of facing enforcement actions remained stable, as did investors’ revealed preferences for trading on US markets. These results go against the legal bonding hypothesis but are consistent with reputational bonding and with market-based accounts of US cross-listing. Our results may contribute to ongoing debate about civil enforcement of securities laws through class actions.